Wounds: physiological mechanisms and factors affecting healing - Rosyid, Fahrun (International Journal of Research in Medical Sciences, 2022)
Wound healing involves cellular, molecular, and biochemical mechanisms that are divided into: three phases of healing: inflammatory, proliferative, and remodeling. Factors that affect wound healing are; 1. local factors, which consist of oxygenation and infection and 2. systemic factors, including: age and gender, sex hormones, stress, diabetes mellitus, obesity, drugs, alcohol and smoking and nutrition.